БОЛАЛАР ФОЛЬКЛОРИДА “БЎРИ” ЗООМОРФ МЕТАФОРАСИНИНГ АНТРОПОЦЕНТРИК ТАҲЛИЛИ (Scientific journal of the Fergana State University, 2023)
The article deals with the anthropocentric analysis of the “wolf” zoomorphic metaphor in children`s folklore.